2017
DOI: 10.37801/ajad2017.14.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender, Risk, and Time Preferences in Farmers' Rice Variety Selection in Eastern India

Abstract: Using data from 5,601 rice farmers in Eastern India, this study examined the role of gender, risk, and time preferences in farmers' rice variety selection in Eastern India. The determinants of the following were estimated: farmers' rice variety selection according to variety type (i.e., modern [non-hybrid], stress-tolerant, hybrid, and traditional), and farmers' main reasons (i.e., yield potential, taste/cooking quality, marketability/affordability, and stress tolerance) for choosing a rice variety. A multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Consequently, participatory variety selection should include the opinions of male and female farmers. Surveys among rice-producing farmers in India reported gender differences in trait preferences and variety selection (Mehar et al, 2017). Tegbaru et al (2020) identified gender-shared and distinct varietal traits in maize.…”
Section: Serial Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, participatory variety selection should include the opinions of male and female farmers. Surveys among rice-producing farmers in India reported gender differences in trait preferences and variety selection (Mehar et al, 2017). Tegbaru et al (2020) identified gender-shared and distinct varietal traits in maize.…”
Section: Serial Nomentioning
confidence: 99%
“…Farmer participatory plant breeding or variety selection has been used especially in marginal crops and environments as an important approach to identify varieties adapted to different environments and the needs of different end-users (Adeniji and Aloyce, 2013;Dinssa et al, 2020;Fufa et al, 2010;Ndinya et al, 2020). It is important to consider gender preferences in variety selection because there may be gender differences in trait preferences and rankings (Mehar et al, 2017). Gender-disaggregated participatory maize (Zea mays) variety trials conducted in Benin, Nigeria, and Mali identified gender-shared and distinct varietal traits (Tegbaru et al, 2020).…”
mentioning
confidence: 99%
“…Hong Kong prefers long-grain, low-amylose rice with a softer gel consistency, while sticky rice is preferred in Laos, Korea, and Japan (Juliano, 1993). Customers in North India favour rice with aromatic long grains (Mehar et al 2017). To satisfy the market's expectations for rice of varied desirable qualities that are locationspeci c, it is necessary to investigate grain quality criteria.…”
Section: Introductionmentioning
confidence: 99%